PELATIHAN PENYUSUNAN SURAT LAMARAN KERJA BERBAHASA INDONESIA YANG PROFESIONAL BAGI MAHASISWA TEKNIK MESIN POLITEKNIK NEGERI MEDAN - Nirmawan -; Devika Adelita; Mahyuni Harahap; Muhammad Balyan (Jurnal Masyarakat Berdikari dan Berkarya (Mardika), 2026)
The community service program aims to improve the knowledge and skills of Mechanical Engineering students at Medan State Polytechnic in compiling professional Indonesian job application letters in accordance with linguistic rules and the needs of the workplace. The implementation method used is participatory training. The results showed an increase in the participants' abilities, which is indicated by an increase in the average score from pretest to post-test and the acquisition of an N-Gain score in medium category. Most participants were able to create job application letters that meet the criteria in terms of writing systematic, language accuracy use, and professionalism of content. This training activity is effective in improving students' competence in professional written communication, especially in compiling job application letters that are in accordance with the demands of the workplace.